2013
DOI: 10.1245/s10434-012-2856-7
|View full text |Cite
|
Sign up to set email alerts
|

Wound Complications after Inguinal Lymph Node Dissection for Melanoma: Is ACS NSQIP Adequate?

Abstract: Background In the treatment of melanoma, inguinal lymph node dissection (ILND) is the standard of care for palpable or biopsy-proven lymph node metastases. Wound complications occur frequently after ILND. In the current study, the multicenter American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) was utilized to examine the frequency and predictors of wound complications after ILND. Methods Patients with cutaneous melanoma who underwent superficial and superficial with deep IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Glarner, et al reported that wound complications rates after inguinal lymph node dissection for melanoma are much lower according to ACS NSQIP compared to single institution data because the ACS NSQIP definition of wound occurrences does not include seroma, hematoma, lymph leak or skin necrosis (15). Similarly, Eck and colleagues demonstrated that ACS NSQIP reports higher morbidity rates after breast conserving surgery compared to mastectomy because it includes reoperation for positive margins as a complication (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glarner, et al reported that wound complications rates after inguinal lymph node dissection for melanoma are much lower according to ACS NSQIP compared to single institution data because the ACS NSQIP definition of wound occurrences does not include seroma, hematoma, lymph leak or skin necrosis (15). Similarly, Eck and colleagues demonstrated that ACS NSQIP reports higher morbidity rates after breast conserving surgery compared to mastectomy because it includes reoperation for positive margins as a complication (16).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, key outcome measures for certain operations are not captured by ACS NSQIP (15-18). An example of this limitation is pancreatic fistula following pancreatectomy.…”
mentioning
confidence: 99%
“…Some of the common factors associated with surgical complications such as smoking, recent weight loss, and serum albumin concentrations [22] were not recorded. Nonetheless, in general, the subjects were relatively healthy therefore recent weight changes or abnormalities in albumin were unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of NSQIP in capturing clinically relevant postoperative complications have also been noted for melanoma, thyroid, and pancreatic surgery. [6][7][8] In another study of patients undergoing breast reconstruction or breast reduction, Khavanin and colleagues compared NSQIP to the Tracking Operations and Outcomes for Plastic Surgeons (TOPS) database. 9 The authors found that compared to TOPS, NSQIP missed surgical complications and was not able to define the complications as specifically as TOPS.…”
mentioning
confidence: 99%